L-Carnitine Treatment of Adult Rats With Busulfan-Induced Oligospermia - Owain, Fahad Saber; Mejbel, Elham Ahmed; Farhan, Rana Salim; Saleh , Eman Naji (Indonesian Journal on Health Science and Medicine, 2024)
Abstract. The purpose of this research was to examine the effects of L-carnitine treatment on adult rats that had busulfan-induced oligospermia. In our experiment, we used twenty-one adult male rats, each weighing around 200 g. Three groups of rats were used for the experiments: The first set of subjects, called the control group, had DMSO administered intraperitoneally and 1 mL of pure water gavaged orally once daily. The second group received 20 mg/kg of busulfan (Bus) administered IP once daily along with a daily oral gavage of 1 ml of distilled water. The third set of subjects received a single I.P. of busulfan along with L-carnitine (L-car) and busulfan administered orally. One day after busulfan injection, L-carnitine were administered for a duration of 28 days at 350 mg/kg.bw. After dissecting, the epididymis and testis were meticulously removed and weighed, along with any excess fat and blood. The spermatozoa were taken from the removed caudal epididymis and incubated in PBS medium containing at 37C for 5 minutes, this used for counting and checking abnormalities. MDA and GSH were also estimated in testes tissues by using HPLC. The administration of BU resulted in a substantially testes weight, and relative testes weight (p <.05) as compared to the control group. testes weight, and relative testes weight were all markedly improved with L-carnitine administration as compared to G2. after administering BU, sperm count and motility were significantly lower (p <.05) compared to G1. There was a significant improvement in motility, sperm count, and abnormalities with L-carnitine administration compared to G2. after BU was administered, MDA were considerably higher and GSH significantly lower (p <.05) as compared to G1. The results of measuring oxidative stress indicators were dramatically improved with L-carnitine administration when contrasted with G2. In conclusion, Busulfan may have a negative impact on male fertility if taken alone, but when combined with L-carnitine, the drug's cytotoxic effects can be mitigated, protecting both testis and semen. Highlights: L-carnitine Treatment: Significantly improved testis weight and sperm quality in busulfan-treated rats. Oxidative Stress Reduction: L-carnitine mitigated increased MDA levels and restored GSH in testicular tissue. Fertility Protection: Co-administration of L-carnitine reduced the cytotoxic effects of busulfan on male fertility. Keywords: L-carnitine, busulfan, oligospermia, male fertility, oxidative stress